Analisis Sistem Informasi Administrasi Kependudukan Dalam Pencetakan Kartu Tanda Penduduk Elektronik (E-KTP) - Zulfa, Ira; Septima, Richasanty; Gemasih, Husna; Eliyin, E; Dzakiansyah, D (LPPM STIKOM Tunas Bangsa, 2024)
In order to increase the effectiveness and efficiency of population administration, the government has developed a population administration information system (SIAK). SIAK is an integrated information system used to manage population data. The Population Administration Information System (SIAK) is one of the systems used in printing Population Identity Cards (KTP) in Indonesia. In conducting research at the Population and Civil Registration Service of Takengon city, the method used is a quantitative research method with data collection techniques using a goggleform-based questionnaire. The method analysis used in this research is Partial Least Square (PLS). Secondary data collection methods provide a basis for understanding aspects of population administration in terms of documents and forms used in SIAK. It is important to ensure that the data collected comes from legitimate and trustworthy sources. This system has a very important role in managing data and information related to the population of an area. Implementing this system is not easy, and various challenges such as suboptimal data quality, information security, and integration with other systems are the main focuses that need to be overcome. However, information technology has great potential to transform public administration to be more efficient, transparent, and responsive to society's needs.